دراسة فطريات البياض الدقيقي (Erysiphaceae ) على بعض نباتات الفصيلة القرعية (Cucurbitaceae) - علي نوال (Latakia University Journal -Biological Sciences Series, 2018)
أظهرت دراسة الأنواع الاقتصادية الهامة التابعة للفصيلة القرعية إصابة /8/ أنواع بفطريات البياض الدقيقي, خمسة أنواع منها مصابة بالفطر Erysiphe cichoracearum فقط, وثلاثة أنواع (الخيار, الكوسا, القرع) كانت مصابة بالنوعين الفطريين معاً: Erysiphe cichoracearum وSphaerotheca fuliginea كما أظهرت الدراسة تواجد الفطريات السابقة بطورها الكونيدي فقط على جميع عوائلها المدروسة طوال العام, بينما غاب الطور الجنسي حيث لم تتشكل الثمار الزقيّة نهائياً . كما بينت النتائج أن نسبة إنتاش الأبواغ الكونيدية للنوع Sphaerotheca fuliginea كانت أعلى مما كانت عليه لدى النوع Erysiphe cichoracearum ونتج عن ذلك سيادة الفطر Sphaerotheca fuliginea على الفطر Erysiphe cichoracearum The survey study has shown that /8/ host plants were found to be infected with powdery mildew, five of then were infected by Erysiphe cichoracearum only. Three Cucurbita maxima - Cucurbita pepo L., Cucumis sativus L. were infected by two fungi species at the same time (Sphaerotheca fuliginea and Erysiphe cichoracearum). It seems that the presence of fungi species on their respective host plant was only in the conidial stage around the year (without any formation of Cleistothecium). The results showed an increased conidial germination by Sphaerotheca fuliginea comparing to Erysiphe cichoracearum. Consequently the species Sphaerotheca was dominant on the leaf surface of host plant comparing to the other fungi species Erysiphe cichoracearum